Archaeology in the Adriatic. From the Dawn to the Sunset of Communist Ideologies - Cella, Elisa; Gori, Maja; Pintucci, Alessandro (Ex Novo: Journal of Archaeology, 2016)
By adopting historical and sociological approaches to archaeology, this paper focuses on the development of archaeology in Albania and Yugoslavia and their relation first to fascism and then to communism and socialist regimes. Identity issues based on archaeological discourse in former Yugoslavia and Albania are often perceived and regarded by western scholarship as extreme distortions and abuses of archaeological practice to promote nationalism. By providing a comparative and diachronic perspective, this paper aims to demonstrate that the way in which a society relates to its past is a complex phenomenon, and that political uses of archaeology in the western Balkans cannot be associated entirely with socialist regimes and communist ideologies. It is argued that different uses of archaeology are the product of a complex interaction between the development of archaeological discipline and historical, social and cultural trajectories.